Health benefits of traditional Chinese sports and physical activity for older adults: A systematic review of evidence - Yucheng Guo; Haiyang Shi; Dinghai Yu; Pixiang Qiu (Elsevier, 2016)
Background: Traditional Chinese sports and physical activities (PAs) have a long history and are practiced by millions of Chinese. However, relatively few systematic reviews of the scientific evidence for their health benefits, especially for older Chinese adults, have been undertaken. Evidence acquisition: Between January and March 2016, a systematic search was conducted using the CNKI and PubMed databases to identify studies published between 2000 and 2015. Studies were selected for review if they were designed specifically to evaluate the health benefits of traditional Chinese sports and PAs in adults aged 50 years and older in the Mainland of China. The studies included observational, uncontrolled, and randomized and controlled designs. Papers published without an English title or abstract were excluded. Evidence synthesis: The initial search identified a total of 229 studies. After removing duplicates and studies that did not meet the inclusion/exclusion criteria, 95 studies were selected for review. Special attention was given to studies of the most commonly practiced activities: Tai Ji Quan, Qigong, and Yangko exercises. A positive association between these types of exercise and health benefits was noted for healthy older adults and those with chronic diseases. Evidence on other types of activities was less clear due to the limited number of studies conducted. Conclusion: There is promising evidence that traditional Chinese sports and PAs provide many health benefits for older Chinese adults. While additional scientifically rigorous research is warranted, promoting these traditional and culturally-based sports and PAs as forms of behavioral medicine in primary and secondary prevention of diseases among the aging Chinese population will help fulfill an urgent public health need.